THE POLITICS OF RELIGIOUS PARTIES IN PAKISTAN: AN ANALYSIS - Muhammad Rizwan; Hafiz Nasir-Ud-Din; Shahab Ali (ASIAN Journal of International Peace & Security (AJIPS), 2020)
Present research work is an effort to describe the nature of the relationship between religion and politics in the society of Pakistan. It is generally agreed that Two Nations Theory provided a solid foundation for the religion in the societal framework of the country. It has been incorporated as a guiding standard for the political system and constitutional mechanism in Pakistan. Nevertheless, several régimes, individuals and political parties have practiced the religion for their pursuit of political legitimacy and power. In addition to this, the growing influence of religious parties in the politics of Pakistan has subsequently contributed to consciousness rising sectional fights, harassment of religious minorities or disempowerment of certain religious leaders and institutions, etc. Unfortunately, on most of the occasions, Islam, the religion of peace and tolerance, has practiced by the religious parties either to avoid public pressure or to gain political power.